1977
DOI: 10.1084/jem.146.5.1234
|View full text |Cite
|
Sign up to set email alerts
|

Specific enrichment of the suppressor T cell bearing I-J determinants: parallel functional and serological characterizations.

Abstract: Recent evidence indicates that determinants controlled by a locus (Ia-4 locus) mapped in I-J subregion of mouse H-2 major histocompatibility complex are selectively expressed on a functional subpopulation of peripheral T lymphocyte, which is endowed with a role to suppress the antibody and immunoglobulin production (1-3). 1 Unlike other/-region associated (Ia) antigens, which are primarily detectable on B cells, the products of Ia-4 locus are not found on B cells, but are uniquely expressed on T cells (1, 4). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 20 publications
5
40
0
Order By: Relevance
“…This finding favors the Ts of the KLH-specific Ts reported by Okumura et al (10). In addition, as reported by Tada et al (13) KLH-specific Ts are nylon-wool adherent.…”
Section: +supporting
confidence: 79%
See 2 more Smart Citations
“…This finding favors the Ts of the KLH-specific Ts reported by Okumura et al (10). In addition, as reported by Tada et al (13) KLH-specific Ts are nylon-wool adherent.…”
Section: +supporting
confidence: 79%
“…The data in Table 2 show that the Ts of contact hypersensitivity are also nylon-wool adherent. From these results it seems likely that the nature of the syninduced Ts in DNFB-specific hypersensitivity is similar to that of the Ts of antibody production (10,14), except for the form of the antigen-binding receptors.…”
Section: +mentioning
confidence: 68%
See 1 more Smart Citation
“…variety of antigenic systems have been shown to involve T cells that bear determinants encoded by the I-J subregion of the H-2 gene complex (16,(23)(24)(25)(26). The I-J phenotype of pork insulin-specific suppressor cells was evaluated next.…”
Section: Requirement For I-j + Cells For Suppression Suppressor Pathmentioning
confidence: 99%
“…First, the antibody activity was tested on the suppressor T cells of various strains of mice by a cytotoxic assay. It has been demonstrated that antigen-specific suppressor T cells enriched by antigen-coated dishes or columns bear the I-J products (13,14). By using the enriched suppressor T cells, it is clearly demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 88%